2004
DOI: 10.1191/0961203304lu1057oa
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients with systemic lupus erythematosus in intensive care unit

Abstract: The objective of the study was to identify the causes, outcome and prognosis of severe illness in patients with systemic lupus erythematosus (SLE) requiring intensive care unit (ICU) care in a University Hospital over a five-year period. The design was a cohort study. Forty-eight SLE patients requiring ICU management over a five-year period (January 1997-December 2001) were studied prospectively. Of 48 patients, 14 (29.2%) died, predominantly with multiorgan dysfunction syndrome (MODS). Patients whose APACHE I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 19 publications
7
45
2
Order By: Relevance
“…However, there are conflicting results regarding the significance of this scoring tool with respect to the outcomes of ICU patients. Although previous studies have demonstrated that the Apache II score is a suitable predictor of the outcomes in patients admitted to the ICU (9,11,13,14,17,24,25), this observation has not been confirmed in other studies (3,26); the latter studies reported that the Apache II score is not independently, or only weakly, associated with mortality. Therefore, we performed a careful analysis of the Apache II score, which subsequently demonstrated a strong correlation between an increased Apache II score and a poor outcome in our cohort, supporting the use of this tool in patients with rheumatic diseases admitted to the ICU.…”
Section: Discussionmentioning
confidence: 82%
“…However, there are conflicting results regarding the significance of this scoring tool with respect to the outcomes of ICU patients. Although previous studies have demonstrated that the Apache II score is a suitable predictor of the outcomes in patients admitted to the ICU (9,11,13,14,17,24,25), this observation has not been confirmed in other studies (3,26); the latter studies reported that the Apache II score is not independently, or only weakly, associated with mortality. Therefore, we performed a careful analysis of the Apache II score, which subsequently demonstrated a strong correlation between an increased Apache II score and a poor outcome in our cohort, supporting the use of this tool in patients with rheumatic diseases admitted to the ICU.…”
Section: Discussionmentioning
confidence: 82%
“…In the literature, reports on rheumatic diseases are available, for example on systemic lupus erythematosus, dermato-polymyositis, rheumatoid arthritis, and vasculitis (16)(17)(18)(19)(20)(21)(22). However, data on these diseases cannot be applied to patients with WG, as it is a very different disease.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that with earlier diagnosis and earlier adequate immunosuppressive therapy, stabilization of the disease might have been possible, and ICU admission might not have been necessary. The situation with WG patients differs from patients with other rheumatic diseases, who sometimes need ICU treatment several years after the diagnosis was made, mainly due to infections after long periods of immunosuppressive therapy (16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that not infected patients with SLE admitted to the ICU with lupus flares, exhibit high mortality rates (75-95%), and nosocomial acquired infections are a relevant complication in most cases. These reports, as well as others (Alzeer et al, 2004), highlight the importance of pneumonia and bacterial sepsis of unknown origin as the most frequent reason for admission to ICU, and their relationship with poor outcomes.…”
Section: Humoral Immunitymentioning
confidence: 59%